No Difference in Behavioral and Self-Reported Outcomes for Simultaneous and Sequential Bilateral Cochlear Implantation: Evidence From a Multicenter Randomized Controlled Trial - Kraaijenga, Véronique J. C.; Ramakers, Geerte G. J.; Smulders, Yvette E.; van Zon, Alice; Free, Rolien H.; Frijns, Johan H. M.; Huinck, Wendy J.; Stokroos, Robert J.; Grolman, Wilko (Frontiers in Neuroscience, 2019)
Objective: The primary aim of this study was to longitudinally compare the behavioral and self-reported outcomes of simultaneous bilateral cochlear implantation (simBiCI) and sequential BiCI (seqBiCI) in adults with severe-to-profound postlingual sensorineural hearing loss. Design: This study is a multicenter randomized controlled trial with a 4-year follow-up period after the first moment of implantation. Participants were allocated by randomization to receive bilateral cochlear implants (CIs) either, simultaneously (simBiCI group) or sequentially with an inter-implant interval of 2 years (UCI/seqBiCI group). All sequential patients where encouraged to use their hearing aid on the non-implanted ear over of the first 2 years. Patients were followed-up on an annual basis. The primary outcome was speech perception in noise coming from a source directly in front of the patient. Other behavioral outcome measures were speech intelligibility-in-noise from spatially separated sources, localization and speech perception in quiet. Self-reported outcome measures encompassed questionnaires on quality of life, quality of hearing and tinnitus. All outcome measures were analyzed longitudinally using a linear or logistic regression analysis with an autoregressive residual covariance matrix (generalized estimating equations type). Results: Nineteen participants were randomly allocated to the simBiCI group and 19 participants to the UCI/seqBiCI group. Three participants in the UCI/seqBiCI group did not proceed with their second implantation and were therefore unavailable for follow-up. Both study groups performed equally well on speech perception in noise from a source directly in front of the patient longitudinally. During all 4 years of follow-up the UCI/seqBiCI group performed significantly worse compared to the simBiCI group on spatial speech perception in noise in the best performance situation (8.70 dB [3.96 – 13.44], p < 0.001) and localization abilities (largest difference 60 degrees configuration: -44.45% [-52.15 – -36.74], p < 0.0001). Furthermore, during all years of follow-up, the UCI/seqBiCI group performed significantly worse on quality of hearing and quality of life questionnaires. The years of unilateral CI use were the reason for the inferior results in the UCI/SeqBiCI group. One year after receiving CI2, the UCI/seqBiCI group performance did not statistically differ from the performance of the simBiCI group on all these outcomes. Furthermore, no longitudinal differences were seen in tinnitus burden prevalence between groups. Finally, the complications that occurred during this trial were infection, dysfunction of CI, facial nerve palsy, tinnitus and vertigo. Conclusion: This randomized controlled trial on bilaterally severely hearing impaired participants found a significantly worse longitudinal performance of UCI/seqBiCI compared to simBiCI on multiple behavioral and self-reported outcomes regarding speech perception in noise and localization abilities. This difference is associated with the inferior performance of the UCI/seqBiCI participants during the years of unilateral CI use. After receiving the second CI however, the performance of the UCI/seqBiCI group did not significantly differ from the simBiCI group. Trial Registration: Dutch Trial Register NTR1722.